Design and modelling of Heinz Isler’s Sicli shell - Chuang, Chu-Chun; Chilton, John (2016)
In 1969 a thin concrete shell roof designed by the master shell builder Heinz Isler was erected for the fire extinguisher manufacturer Sicli, SA, in Geneva, Switzerland. From this research carried out at the Heinz Isler Archive at ETH Zürich, it was found that more, previously unrevealed, alternative proposals and physical models were employed to accomplish this project. This paper describes an investigation of the original physical modelling process of the Sicli shell and discusses the infinite potential of form-finding methods for shaping a good shell. Four alternative free-form design schemes proposed by Isler for the Sicli shell, in addition to the final chosen hanging cloth modelling approach, are introduced and discussed. The actual construction details of the Sicli shell will be reviewed with regard to both architectural and engineering perspectives. In conclusion, more research to be carried out on the valuable legacy of Isler’s form-finding techniques is suggested.